Refleksi Dalam Seni Patung - Eko Sunarto (Ars: Jurnal Seni Rupa dan Desain, 2010)
As part of  a community, an artist can’t be released from the influencing phenomena occurred in the community. A work of  art is a reflection of the inner drive and emotion from its creator. In getting in touch with the community, the writer deeply touched by what really happened inside currently. The advanced technology proves that it cannot only make man think rationally but also  drags him away from his rationality. The upcoming high competition in all human life aspects has recently raised the human egos. Things are seen materially from profit and loss. Those who expect prosperity instantly would not do something more real to get merits. This sets them up in a game made by others who take advantage of  other people’s confusion. Alike phenomena are plenty to be revealed; even it never lasts, because of  its dynamic nature of  the community. Swimming pool is used as a metaphoric symbol of  depiction on the importance of  “reflection” to the human beings either individual or as a group. The form of  swimming pool is symbolically presented in a different way. To attain a natural look without any distortion, a view point has to be made. The beam reflection of  water shadow is made to make the situation inside the room more alive. This work is created to invite the art lovers enjoy the swimming pool nuance without getting drenched as well as having self  introspection. Amongst the sculptures presented, one of them could be a reflection of  oneself. Keyword:  reflection, introspection